Autonomy and the Common Weal - Danis, Marion (The Hastings Center report, 1991)
When health care providers make decisions to use resources, their devotion to the patient at hand must be mediated by a framework that puts individual autonomy and social equity into focus simultaneously. The concept of citizenship yields such a framework.